Options for Managing Maine’s Fisheries: Traditional Fisheries Management - Townsend, Ralph (Maine Policy Review, 1996)
Ralph Townsend discusses the historic evolution of fisheries management as well as more current trends toward co-management in Maine’s groundfisheries. Looking at successful experiences with co-management, he wonders whether current efforts in Maine’s lobster industry will be successful without tackling the tough issue of access limitation.